Studies on carbon-13 turnover in eggs and blood of commercial layers - Denadai, Juliana Célia [UNESP] (2006)
This paper aimed at evaluating the influence of diets containing different isotopic values of carbon-13 turnover on the half-life of egg (yolk + albumen), yolk and albumen individually, and blood of poultry using δ‰ 13C isotopic variation. Commercial layers fed four experimental isocaloric and isonitrogenous diets (RC 4, RC 3, RMC 4 and RMC 3) containing different isotopic values, during an experimental period of 56 days. Turnover of the studied tissues was influenced by the experimental diets. Blood and albumen were more influenced by dietary treatments as compared to egg and yolk. The RMC 3 diet induced better performance (better feed intake and higher egg production) due faster rate of carbon substitution than the RC 4 diet, and lower half-life for egg (yolk + albumen), yolk, and albumen.